2017
DOI: 10.3171/2016.2.jns152120
|View full text |Cite
|
Sign up to set email alerts
|

Role of terminal and anastomotic circulation in the patency of arteries jailed by flow-diverting stents: from hemodynamic changes to ostia surface modifications

Abstract: OBJECTIVE The outcome for jailing arterial branches that emerge near intracranial aneurysms during flow-diverting stent (FDS) deployment remains controversial. In this animal study, the authors aimed to elucidate the role of collateral supply with regard to the hemodynamic changes and neointimal modifications that occur from jailing arteries with FDSs. To serve this purpose, the authors sought to quantify 1) the hemodynamic changes that occur at the jailed arterial branches immediately after stent placement an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…Recent laboratory data showed that terminal-type arteries, when jailed, tend to maintain poststenting flow rates similar to the prestenting ones in the acute poststenting phase; this scenario, in turn, seems related to decreased neointimal coverage of the jailed ostia at 3-month control. [15][16][17] In accordance with previous reports, transient symptoms were noted during the first follow-up months. 18 In our opinion, they were not related to in situ thrombotic events but rather to hemodynamic parameters.…”
Section: Discussionsupporting
confidence: 76%
“…Recent laboratory data showed that terminal-type arteries, when jailed, tend to maintain poststenting flow rates similar to the prestenting ones in the acute poststenting phase; this scenario, in turn, seems related to decreased neointimal coverage of the jailed ostia at 3-month control. [15][16][17] In accordance with previous reports, transient symptoms were noted during the first follow-up months. 18 In our opinion, they were not related to in situ thrombotic events but rather to hemodynamic parameters.…”
Section: Discussionsupporting
confidence: 76%
“…12 As described by Iosif and colleagues, jailed cortical branches may find a new hemodynamic balance with leptomeningeal anastomosis, and fluctuate over time, maintaining some laminar direct perfusion through the stent with continuous changes in caliber. 13,14 However, complications may occur in the acute phase. In our case, it could be explained by the fact that the FD stent deployed in the upper branch was too long and covered too many branches (i.e., the anterior, temporal, and lower branch), so this might have prevented a new hemodynamically effective balance between leptomeningeal and direct perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…When collaterals are not readily available, as may be expected in a number of MCA bifurcation situations for example, covered branches tend to remain patent. 27 What remains unpredictable, at least in our experience, is why, under conditions of continued branch patency, the associated aneurysm sometimes disappears and sometimes does not. There is evidence to suggest that collateral circulation continues to evolve well beyond the typical 12-month posttreatment efficacy benchmark, contributing to progressive occlusion of branch-associated aneurysms.…”
Section: Discussionmentioning
confidence: 81%
“…Tables of these relationships are available. 16 The above model is highly conservative because it forbids a number of realistic and often highly effective in vivo adoptive changes, 27 all of which are directed at minimizing ⌬I following FD implantation. These include adaptive hypertension, vasodilation in both primary and collateral circuits (decrease in R, R brain , and r), and, most important, long-term increases in collateral efficiency (further drop in R).…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation